Neutron reflection study of bovine beta-casein adsorbed on OTS self-assembled monolayers. - Fragneto, G; Thomas, R; Rennie, A; Penfold, J (1995)
Specular neutron reflection has been used to determine the structure and composition of bovine beta-casein adsorbed on a solid surface from an aqueous phosphate-buffered solution at pH 7. The protein was adsorbed on a hydrophobic monolayer self-assembled from deuterated octadecyltrichlorosilane solution on a silicon (111) surface. A two-layer structure formed consisting of one dense layer of thickness 23 +/- 1 angstroms and a surface coverage of 1.9 milligrams per square meter adjacent to the surface and an external layer protruding into the solution of thickness 35 +/- 1 angstroms and 12 percent protein volume fraction. The structure of the (beta-casein) layer is explained in terms of the charge distribution in the protein.